Serving the Underserved: Medical Residents’ Experiences Working with Ventura County’s Backpack Medicine Program - Charpentier, Nicole; Damato, Faith; Dawson, Jacob; Enochs, Cade; Friedl, Paulina; Meade, Lena; Mendoza, Fatima; Ninh, Alison; Nunez, Erik; Panico, Paige; et al. (CBR@CSUCI: An annual volume of community-based research, 2025)
EXECUTIVE SUMMARY Research origins and goals: The research was conducted through a partnership between the Health Science Program at California State University Channel Islands (CSUCI) and Backpack Medicine. Interviews were conducted by students as part of their senior Capstone project. The main focus of the interviews was to gather data based on the experiences of those involved with Backpack Medicine and to learn about how they serve the homeless populations in Ventura County communities. The findings of the research were analyzed to pinpoint specific health issues within these communities, the work Backpack Medicine does to address these issues, and the work that they could be doing in the future. Research methods: Research included qualitative interviews conducted with seven participants, all with varying roles within the Backpack Medicine organization in order to provide a wide enough range of experiences. Initial and current involvement: Most of the members involved with Backpack Medicine have previous medical experience or have worked with the homeless population. Some have been in a position where they have seen how much those who are homeless struggled with health issues and social stigmas. In addition to the medical residents who provide medical care through Backpack Medicine, there is also support from law enforcement and drivers that take patients to appointments and others who address administrational aspects. Sources of satisfaction and challenge: Respondents felt satisfied when their patients returned for follow up treatment and/or continued to progress in their healthcare goals. Individuals that work in Backpack Medicine stated that some challenges they saw their patients deal with were motivation, the negative imagery on the homeless population, isolation from pandemic that extended to loss of jobs, and the difficulty of continuing to seek help. Future involvement: All interviewed participants stated that they want to continue their work with Backpack Medicine. Many wanted to add to their involvement and better the public's perception of the homeless population. Needed support and encouragement: Participants identified that resources and services must be more readily available to the populations they serve in order to properly care for their needs in the future.